The first inhabitants of Arcadia - Bursk, Christopher (University of Arkansas Press poetry series., 2006)
"Herman Melville, Matthew Arnold, Sarah Orne Jewett, Dusty Rhodes, and Hoyt Wilhelm skinny-dip and pick up gondoliers and cut figure eights into the ice in Christopher Bursk's new collection. But the main cast of characters for these poems is the alphabet itself, "the first inhabitants of Arcadia, / now homesick, curious exiles from Eden." Here are a boy's first investigations into the nature of language as he studies the backs of baseball cards, and a young man's infatuation with the "F-word". The poems carry us from the picket line and a county jail and the canals of Venice all the way to a hotel room and a father's suicide note. They conclude with September 11 and a confrontation of the potential and painful limits of language.